AN ANALYSIS OF PATTANIâS STUDENTS PRONUNCIATION IN PRONOUNCING ENGLISH FRICATIVE CONSONANTS AT UIN LAMPUNG - mulyadi, wahyuni wulandary (STKIP Muhammadiyah Pringsewu, 2018)
This research is aimed to find out common pronunciation errors in pronouncing English fricative thus, to find how many global and local errors in pronouncing English fricative based on Communicative Effect Taxonomy, and to find the causes of pronunciation error made by Pattaniâs students. This research used qualitative research. The result shows that the common error is fricative [Ã°]. Then, some causes of errors by the subjects according to interlingual and intralingual transfer, such as: first, fricative [Î¸], [Ã°], [Æ·] are unshared sounds specific to English, [Î¸] and [Ã°] were realized as stop [t] and [d]. Â Keywords: Pattaniâs Students, Pronunciation, Fricative Consonants.